The man who lived underground a novel - Wright, Richard 1908-1960 (Library of America, 2021)
"An explosive, previously unpublished novel by Richard Wright, written in the 1940s, at the height of his creative powers"--
Enthält auch Richard Wrights Essay "Memories of my grandmother"
Keywords: Fiktionale Darstellung